2019
DOI: 10.1167/iovs.18-24389
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography Quantitative Assessment of Exercise-Induced Variations in Retinal Vascular Plexa of Healthy Subjects

Abstract: Citation: Vo Kim S, Semoun O, Pedinielli A, Jung C, Miere A, Souied EH. Optical coherence tomography angiography quantitative assessment of exercise-induced variations in retinal vascular plexa of healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 42 publications
2
21
1
2
Order By: Relevance
“…Although autoregulatory mechanisms in the retina tend to maintain a constant blood flow over a wide range of perfusion pressures, blood flow can decrease beyond the compensation range 23 , 24 . Previous studies in adults showed that macular perfusion decreases in the superficial retinal layer after exercise, and that VD remains stable in the deep layer 6 , 20 . This discrepancy between the variation trend of RVD in superficial and deep layers after exercise may be attributable to differences in the elasticity and hardness of the fundus vessels between children and adults, which may lead to differences in autoregulatory ability 17 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although autoregulatory mechanisms in the retina tend to maintain a constant blood flow over a wide range of perfusion pressures, blood flow can decrease beyond the compensation range 23 , 24 . Previous studies in adults showed that macular perfusion decreases in the superficial retinal layer after exercise, and that VD remains stable in the deep layer 6 , 20 . This discrepancy between the variation trend of RVD in superficial and deep layers after exercise may be attributable to differences in the elasticity and hardness of the fundus vessels between children and adults, which may lead to differences in autoregulatory ability 17 .…”
Section: Discussionmentioning
confidence: 93%
“…Alnawaiseh et al 10 reported that peripapillary and parafoveal flow densities decreased significantly after exercise. Vo Kim et al 6 also reported that the vessel density (VD) at the level of the retinal superficial layer, from 3 μm below the internal limiting membrane (ILM) to 15 μm below the inner plexiform layer (IPL), were decreased after exercise while the fractal dimension in the retinal deep layer, from 15 to 70 μm below the IPL, were significantly increased. Hayashi et al 7 found that the blood flow and vascular conductance of retinal arterioles remained stable while ocular blood flow increased in the retina and choroid during physical exercise.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Physiological changes of the retina due to physical exercise Recently, Vo Kim et al showed that in employing OCT angiography in young individuals, a reduction of vessel density can be observed in the superficial vascular plexus of the macula, most possibly due to an increase in intraocular pressure during exercise [7]. At the same time, the fractal dimension of the deep capillary network increased after exercise, suggesting vascular recruitment.…”
Section: Physiological Changes Of the Fundus Circulation Due To Physimentioning
confidence: 99%
“…In der Auswertung lag nicht von allen Patienten ein mit der OCT-A-Messung zeitgleich erhobener Blutdruckwert vor, sodass für eine statistische Auswertung des Blutdrucks als Confounder die Fallzahl nicht ausreichte. In einer anderen Arbeit wurde jedoch belegt, dass der Blutdruck zum Zeitpunkt der Messung keinen direkten Einfluss auf das Messergebnis der FAZ hat [49]. In unserer Arbeit ist aber trotzdem sichergestellt, dass keiner der Probanden vasoaktive Medikamente eingenommen hat oder dass eine vaskuläre Grunderkrankung, wie z.…”
Section: Diskussionunclassified